Analisis Brand Awareness Produk Ms Glow Di Desa Poka (Studi Pada Masyarakat Desa Poka) - Sitorus, Marisa Evi; Telussa, Sandra (Jurnal Ilmu Komunikasi Pattimura, 2023)
Abstract: The importance of Brand Awareness for a skincare Product is currently a special concern for every user. One of the most popular Skincare products among the public is Skincare MS Glow. From the explanation above. This Study aims to determine the ectent of Brand Awareness of MS Glow products in Poka Village Communities. This Study aims to find out which half of the Brand awareness of MS Glow Products in the people of Poka Village, Ambon City. This Research is a qualitative descriptive study with an individual unit of analysis, namely people who have used MS Glow products. This study uses data collection techniques in the form of interviews, to 10 sources of participatory observation, and documentation. The data analysis technique used in this study is data reduction, displaying data, drawing conclusions. The result showed that the people of poka village were well acquainted with MS Glow skincare products. Brand awareness analysis of the MS Glow brand meets the criteria desired by the poka village community, namely MS Glow is a type of skincare product that has the function of overcoming and treating facial skin. And already has a BPOM certification, the poka village community gets a reminder (Brand Recall) MS Glow skincare products just by looking at the logo slogan and symbol of the product. The goal is to position the brand to the top of the mind in the minds of users. Based on the results of research on the audience process to realize top of mind which cand be seen from the many well-known brands of skincare products at this time, the people of poka village tend to continue to use MS Glow products.